Avaliação crítica de cenários de abandono de poços petrolíferos onshore do nordeste brasileiro - Braga, Igor Pires de Melo (2021)
Oil and gas production dates back to the end of the 19th century, with systematic commercial production starting in the second half of the 20th century, especially with the creation of Petrobras. Thus, thousands of oil wells were drilled in the 1950s. The consequence of this is that these wells are many over 50 years old, and can reach 70 years old, to obtain wells with mechanical and hydraulic integrity problems. Northeast of Brazil has thousands of non-productive oil and gas wells may that be caused by low production, maintenance problems, companies decisions. Many are closed with no observance to the recent plug and abandonment rules of the SGIP (Well Integrity Management System) brought by Regulation ANP 46/2016. So it has been with the main fields of North and Northeastern areas of Brazil. Resolution 46/2016 from ANP controls the general procedures for stablishing a Well Integrity Management System. Thus the new regulation marks the positivation of how to abandon an oil and gas well, always seeking the north of well integrity, aiming the security to the people and to the environment. Then, the non-desirable hydrocarbons flows to the surface or between different zones (formations) will generate strong accountability, at present, for the field operators since plug and abandonment modern regulations are based on double solidary sets of barriers (CSBs) that aim to make the well as or more intact than virgin formations / reservoirs. Based on the above, this work has as main objective to present a diagnosis of the current level of integrity risk that thousands of wells in the northeast of Brazil can represent for the onshore environment, according to the method given by the Brazilian Petroleum Institute, characterizing the actions that are necessary to make them conform in terms of abandonments. To reach it, this paper presents the recent rules for onshore abandonments in Brazil, also arising from the best international practices in the subject. A parallel is made between the old ANP decrees of 1997 and 2002, analyzing the main changes in the ways of conceiving abandonment interventions, reflecting in the professionalization of practices, operational discipline, safety, and especially the search for economics. The time and cost to abandon a well where mechanical integrity has been sought throughout the entire life cycle is considerably smaller.